Description of the quality of athlete-coach communication in the district Kutai kartanegara East Kalimantan - Rahmat, Rahmat; Irianto, Djoko Pekik; Kurniawan, Fadillah; Ningrum, Novi Resmi (Jorpres (Jurnal Olahraga Prestasi), 2024)
The purpose of this study was to determine the quality of athlete-trainer communication in Kutai Kartanegara Regency, East Kalimantan. The aim of research on the quality of athlete-coach communication is to evaluate and analyze athletes' perceptions of the quality of communication they receive from their coaches. To identify areas of communication that could be improved between athletes and coaches, as well as understand how successful communication can be understood by athletes and impact outcomes. Coaches need to understand better communication with athletes.The method used in this research uses quantitative descriptive. Quantitative descriptive is a research method by collecting data and processing it in a descriptive way. It can also be used to identify factors that influence conclusions about the subject under study. Quantitative descriptive can be used to collect information from populations or individual subjects. This method can also be used to analyze past data to look for patterns or trends in the data. The number of samples in the study were 46 athletes. The instrument used in this study was a questionnaire/questionnaire in the form of a google form.The results of this research noted the results in the quality of communication between athletes and coaches. Open communication with coaches reached 68.8% and expressing opinions when communicating with coaches had a result of 62.5%. Resolving communication problems and exchanging opinions is one of the best ways. The importance of communication in training reached 56.3%. Discussion with athletes had a result of agreeing 43.8%, strongly agreeing 31.3%, strongly disagreeing 6.3%, and disagreeing 18.8%. This helps coaches to understand topics more deeply and increase athletes' ability to solve problems.